Selected Components affecting Quality of Performance Management Systems - Jelínková Lucie; Stříteská Michaela (Elsevier Science BV, 2015)
The paper addresses two basic components of succesful performance measurement and management, namely the identification of an appropriate set of performance measures and factors that created quality of the performance management system. Based on the literature review, the results of previous research studies and case study analysis, the importance of financial and non-financial measures for decision-making is identified. Furthermore, the current trends in financial performance measurement and the specific areas of performance measurement using non-financial indicators are examined. The essence of sucessful performance management is seen in identification of key factors that affecting the quality of the performance management system. Therefore, the attention is paid to this issue.
Vybrané komponenty, které ovlivňují kvality systémů řízení výkonnosti
Keywords: performance measurement; performance management system; factors; financial measures; non-financial measures; měření výkonnosti; systém řízení výkonnosti; faktory; finanční měřítka; nefinanční měřítka